The impact of teachers’ caring behavior on EFL learners’ academic engagement: the chain mediating role of self-efficacy and peer support - Manli Wu; Jingyi Cai (BMC Psychology)
Abstract Background The significance of academic engagement for English as a Foreign Language (EFL) learners has gained increasing attention in recent research. While studies have shown that teachers’ caring behavior positively influences academic engagement, the underlying roles of self-efficacy and peer support remain unexplored. This study examines the impact of teachers’ caring behavior on academic engagement and investigates the chain-mediating effects of self-efficacy and peer support. Methods A survey-based study was conducted with EFL learners from three universities in Xuchang, Henan Province, China. The study utilized the Teachers’ Caring Behavior Scale, English Self-Efficacy Scale, Peer Support Scale, and Utrecht Work Engagement Scale for Students. Data analysis was performed using Partial Least Squares Structural Equation Modeling with SmartPLS 4.0 to examine the relationships among variables. Result The findings indicate that teachers’ caring behavior significantly enhances academic engagement (β = 0.069; p = 0.042). Peer support fully mediated the relationship between teachers’ caring behavior and academic engagement (VAF = 68.56%), while self-efficacy partially mediated this effect (VAF = 45.67%). Furthermore, peer support and self-efficacy jointly functioned as a chain mediator, linking teachers’ caring behavior to academic engagement (VAF = 64.80%). Conclusion The study suggests that teachers’ caring behavior fosters a supportive peer environment, which enhances self-efficacy and ultimately increases academic engagement. These findings provide theoretical support and practical insights for improving academic engagement among EFL learners, emphasizing the importance of teacher support and peer interactions in language learning.